2018
DOI: 10.1038/s41419-018-1161-1
|View full text |Cite
|
Sign up to set email alerts
|

The SGK3-triggered ubiquitin–proteasome degradation of podocalyxin (PC) and ezrin in podocytes was associated with the stability of the PC/ezrin complex

Abstract: Podocyte damage is commonly accompanied by destabilization of the podocalyxin (PC)/ezrin complex. Serum- and glucocorticoid-inducible kinase 3 (SGK3) plays a role in the maintenance of podocyte function, but the details of this role are poorly understood. Herein we demonstrated that SGK3 and its downstream target protein neural precursor cell expressed developmentally downregulated protein 4 subtype 2 (Nedd4-2) triggered PC and ezrin interaction. In adriamycin (ADR)-induced nephritic mice, and after puromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…SGK3 is a serine/threonine protein kinase that is involved in regulating cell proliferation and ion transport ( Lang et al, 2006 ; He et al, 2011 ). Our previous studies have shown that SGK3 inactivation inhibited podocyte cell viability, downregulated the expression of podocin and CD2AP proteins, and increased ubiquitination-mediated degradation of podocalyxin and ezrin ( Peng et al, 2018 ; Yuan et al, 2018 ). The present study demonstrated that the decreased levels of SGK3 were positively correlated with the levels of nephrin in the kidneys of an ADR-nephritis mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SGK3 is a serine/threonine protein kinase that is involved in regulating cell proliferation and ion transport ( Lang et al, 2006 ; He et al, 2011 ). Our previous studies have shown that SGK3 inactivation inhibited podocyte cell viability, downregulated the expression of podocin and CD2AP proteins, and increased ubiquitination-mediated degradation of podocalyxin and ezrin ( Peng et al, 2018 ; Yuan et al, 2018 ). The present study demonstrated that the decreased levels of SGK3 were positively correlated with the levels of nephrin in the kidneys of an ADR-nephritis mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination assays were performed as described ( Yuan et al, 2018 ). Mouse podocytes were treated with ADR (0.2 μg/ml) or transfected with plasmids and MG132 (10 μM) was added for 8 h before collected to prevent proteasomal degradation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ezrin expression can be regulated by miRNAs (34). Moreover, Ezrin can be degraded by the ubiquitination proteasome (35). Here, we found that circCDYL2 bound to Ezrin and upregulated its protein levels, indicating that circCDYL2 might stabilize Ezrin and protect it from degradation.…”
Section: Discussionmentioning
confidence: 72%